An application of the Sakai's theorem to the characterization of H*-algebras - Borut Zalar (International Journal of Mathematics and Mathematical Sciences)
The well-known Sakai's theorem, which states that every derivation acting on a von Neumann algebra is inner, is ,used to obtain a new elegant proof of the Saworotnow's characterization theorem for associative H*-algebras via two-sided H*-algebras. This proof completely avoids structure theory.